Implementation of communicative approach to managerial decision-making - Krasnykov, Yevgen (Management and Entrepreneurship: Trends of Development, 2024)
The article considers the importance of introducing a communicative approach in the process of making managerial decisions in public organizations. The author determines that the modern head of a public organization needs to create an effective communication network to ensure the exchange of information and the adoption of sound management decisions. The author identifies six main channels of organizational communication, such as hierarchy, representation, group briefings, networks, mass and individual communications. The article examines the communicative approach to designing an information system, which includes ten steps provided as recommendations for leaders of public organizations. The author shows the difference between «programmable» and «non-programmable» decisions in the context of their adoption. Programmable solutions are defined as those that can be effectively developed using computer technology, since they are characterized by quantitative measurement of variables and the presence of understandable and unambiguous decision-making rules. On the contrary, non-programmable solutions are defined as those that are more difficult to automate. These are decisions that require human judgment and management decision-making. The author expresses the opinion that unprogrammed solutions may be associated with more complex situations or those that require a creative approach. A rational decision-making model indicates a logical sequence of events in the process of making them. Such a model has been proposed as a tool for systematizing and rationalizing decision-making, which can contribute to more effective management and quality provision of public services. It is substantiated that delays in making managerial decisions can lead to problems in providing public services. The article emphasizes the critical nature of the immediate response to these questions, since their avoidance may adversely affect the activities of a public organization. The role of information in managerial decision-making is defined as key, so the communicative approach allows to improve the processes of decision-making and their perception. The author offers a comprehensive communicative approach that combines reflexive, critical, creative, empathic and evaluative thinking. This approach takes into account the personality of the leader, his communication skills and includes elements of listening, learning, persuading and conducting successful negotiations. It is noted that this approach helps to avoid demotivation of staff and ensures the effective activities of the leadership of a public organization.JEL Classification: H79, J20, M10